Preparation and Characterization of Sulfonated Carbon Cryogel Doped Zinc as a Catalyst for Glucose Ethanolysis to Ethyl Levulinate - Zainol, Muzakkir Mohammad; Roslan, Mohamad Nor Fitri; Asmadi, Mohd; Amin, Nor Aishah Saidina (ASEAN Journal of Chemical Engineering, 2021)
In this study, sulfonated carbon cryogel (CC) doped with zinc was prepared and used as a solid catalyst. Carbon cryogel was prepared by mixing urea and furfural, freeze-drying, and calcination. The CC was then sulfonated and impregnated with zinc (II) nitrate for ethyl levulinate production from ethanolysis of glucose. Experiment results showed that different types of catalyst prepared from CC precursor had different catalytic effects on the ethanolysis of glucose. Sulfonated carbon cryogel doped with zinc (SCC-Zn) which prepared at a calcination temperature of 300 °C showed better performance as a catalyst for the ethanolysis reaction of glucose. In addition, the 10 wt.% of Zn was recommended as optimum loading for the impregnation on the catalyst. The ethyl levulinate yield of 19.6 mol% was obtained at 180 °C for 6 h with 0.15 g catalyst loading and 0.4 g of glucose feed. The selected SCC-Zn catalyst was further characterized by using FTIR, TGA XRD, and SEM-EDX to evaluate its physical and chemical properties as a catalyst.